Electrode plate and battery with same
By introducing a COF-type material layer into the electrode sheets of lithium-ion batteries for full coating, the problems of gas leakage and low adsorption efficiency in lithium-ion batteries are solved, thereby improving the electrochemical performance and cycle life of the batteries.
Patent Information
- Application Number
- CN202420867370.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-24
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2034-04-24
AI Technical Summary
During use, lithium-ion batteries are prone to lithium-ion electrolyte reduction, which generates carbon monoxide and low-carbon hydrocarbon gases. This leads to increased internal pressure in the cell, poor packaging reliability, and affects cycle life and safety. Furthermore, the existing battery structure has low gas adsorption efficiency and poses a risk of leakage.
An electrode structure comprising a current collector, an active material layer, and an adsorption layer is adopted. The adsorption layer uses a COF-type material layer to cover the first surface and sides of the active material layer, especially to fully encapsulate the edge area to prevent gas leakage, and improves conductivity and dynamic performance through the ordered pore structure of the COF material.
It improves gas adsorption efficiency, reduces internal gas leakage in the battery, enhances the battery's electrochemical and cycle performance, and avoids the introduction of metal ions, thereby improving the battery's conductivity and kinetic performance.
Smart Images

Figure CN222320280U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of batteries, and in particular to an electrode plate and a battery having the same. Background Art
[0002] At present, lithium batteries have been widely used in digital products, power tools, new energy vehicles, aircraft, energy storage base stations and other fields due to their advantages such as high capacity, long life, no memory, and environmental friendliness. Lithium-ion batteries are secondary batteries that mainly rely on the insertion and removal of lithium ions between the positive and negative active materials to complete the charging and discharging process. During the use of lithium-ion batteries, since the commonly used lithium-ion electrolyte components are easily reduced at the negative electrode to produce carbon monoxide and low-carbon hydrocarbon gases, in actual use, as the amount of gas increases, the internal pressure of the battery cell increases, resulting in poor packaging reliability of the battery cell, thereby reducing the cycle life of the finished battery cell and affecting the safe use of lithium-ion batteries. At present, many research directions add porous materials to the battery to adsorb the negative electrode gas of the battery to reduce the impact on the battery cycle performance, but the introduction of foreign objects will more or less bring other disadvantages to the battery. In addition, the existing battery or electrode plate structure has a low adsorption efficiency for the generated gas, and there is also a risk of gas leakage.
[0003] In view of this, it is indeed necessary to provide a new technical solution to solve the above technical problems. Utility Model Content
[0004] In view of this, the utility model aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the utility model provides an electrode plate and a battery having the same, which can improve the gas adsorption efficiency and help improve the cycle performance of the battery.
[0005] In order to solve the above technical problems, this application is implemented as follows:
[0006] According to one aspect of the present application, an embodiment of the present application provides an electrode plate, wherein the electrode plate comprises:
[0007] current collector;
[0008] an active material layer, disposed on at least one side surface of the current collector along the thickness direction, the active material layer having a first surface, the first surface facing away from the current collector, and a side surface connected to the first surface formed at an edge of the active material layer;
[0009] An adsorption layer covers at least a portion of the first surface and / or at least a portion of the side surface, and the adsorption layer includes a COF material layer.
[0010] In addition, the electrode plate according to the present application may also have the following additional technical features:
[0011] In some embodiments, the adsorption layer includes a first adsorption layer and a second adsorption layer, the first adsorption layer covers at least a portion of the first surface, and the second adsorption layer covers at least a portion of the side surface;
[0012] The thickness of the first adsorption layer is different from the thickness of the second adsorption layer.
[0013] In some embodiments, the thickness of the first adsorption layer is 1 μm to 5 μm.
[0014] In some embodiments, the thickness of the second adsorption layer gradually becomes thinner along a direction away from the active material layer.
[0015] In some embodiments, the thickness of the second adsorption layer gradually becomes thinner linearly along a direction away from the active material layer.
[0016] In some embodiments, the minimum thickness of the second adsorption layer is a, the maximum thickness of the second adsorption layer is b, a ranges from 0 to 10 μm, excluding 0, and b ranges from 71 μm to 165 μm.
[0017] In some embodiments, the average thickness of the second adsorption layer is 50 μm to 150 μm.
[0018] In some embodiments, the width of the second adsorption layer is 3 mm to 8 mm.
[0019] In some embodiments, the current collector includes a tab region and a coating region, the active material layer covers the coating region, and the tab region is connected to the tab;
[0020] One end of the electrode tab is connected to the second portion of the adsorption layer.
[0021] In some embodiments, the active material layer has a thickness of 70 μm to 160 μm.
[0022] In some embodiments, the thickness of the current collector is 4 μm to 20 μm.
[0023] In some embodiments, the current collector comprises copper foil or carbon-coated copper foil.
[0024] In some embodiments, the COF-based material layer includes a COF material layer or a modified COF material layer.
[0025] According to another aspect of the present application, an embodiment of the present application provides a battery, which includes a positive electrode plate, a separator and a negative electrode plate, wherein the negative electrode plate adopts an electrode plate as described above; the positive electrode plate includes a positive active material area, and the adsorption layer covers the edge of the positive active material area.
[0026] The implementation of the technical solution of the utility model has at least the following beneficial effects:
[0027] In the embodiment of the present application, the provided electrode plate includes a current collector, an active material layer and an adsorption layer which are stacked, wherein the active material layer includes a first surface and a side surface, the adsorption layer can cover the first surface and / or the side surface of the active material layer, and the adsorption layer adopts a COF material layer. Thus, by covering the side surface of the active material layer with the adsorption layer, that is, the adsorption layer can cover the edge area of the active material layer, and the adsorption layer can cover the edge of the positive active material area of the positive electrode plate, so that the edge area of the active material area can be completely covered (wrapped) by the adsorption layer, the leakage of gas (such as oxygen) can be avoided, the phenomenon of gas generated inside the battery leaking from the edge of the electrode plate is reduced, the adsorption efficiency is improved, and thus it is beneficial to improve the electrochemical performance of the battery using the electrode plate. In addition, the adsorption layer of the COF material layer can avoid the introduction of metal ions, which is beneficial to improve the conductivity of the plate, and the highly regular pore structure of the COF material, that is, the ordered pore size and pore structure can enhance the kinetic performance of the battery, which is beneficial to improve the electrochemical performance or overall performance of the battery using the electrode plate.
[0028] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become apparent from the following description, or will be understood through the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The figure shows a schematic diagram of the structure of an electrode plate provided by an embodiment of the utility model;
[0030] Figure 2 The figure shows a schematic diagram of the structure of another electrode plate provided by an embodiment of the utility model;
[0031] Figure 3 The figure shows a schematic diagram of the unfolded structure of the electrode sheet provided by the embodiment of the utility model before winding;
[0032] Figure 4 Shown is a schematic diagram of the unfolded structure of the electrode plate provided in an embodiment of the utility model.
[0033] Description of reference numerals:
[0034] 10-current collector;
[0035] 20-active material layer;
[0036] 30-adsorption layer;
[0037] 31- first part of the adsorption layer; 32- second part of the adsorption layer;
[0038] 40-Pole ear. DETAILED DESCRIPTION
[0039] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.
[0040] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0041] Below, the embodiments of the electrode plates, batteries, etc. of the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0042] If there is no special description, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. If there is no special description, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0043] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0044] refer to Figures 1 to 4 As shown, in some embodiments, the present application provides an electrode plate, which includes:
[0045] Current collector 10;
[0046] The active material layer 20 is disposed on at least one side surface of the current collector 10 along the thickness direction. The active material layer 20 has a first surface, the first surface is away from the current collector 10, and a side surface connected to the first surface is formed at the edge of the active material layer 20;
[0047] The adsorption layer 30 covers at least a portion of the first surface and / or at least a portion of the side surface, and the adsorption layer 30 includes a COF material layer.
[0048] The provided electrode plate includes a current collector 10, an active material layer 20 and an adsorption layer 30 which are stacked in sequence, that is, the active material layer 20 is arranged on at least one side surface of the current collector 10, and the adsorption layer 30 is arranged on the first surface and / or side surface of the active material layer 20.
[0049] The above “active material layer 20 is disposed on at least one side surface of the current collector 10 along the thickness direction” means that the active material layer 20 can be disposed on one surface of the current collector 10 along its own thickness direction, or on two surfaces of the current collector 10 along its own thickness direction. The “surface” here can be the entire area of the current collector 10, or a partial area of the current collector 10. For example, in this embodiment, the surface can be a partial area of the current collector 10, and the remaining area of the current collector 10 can be used to connect the tab 40. This application has no special restrictions on this, as long as the purpose of this application can be achieved.
[0050] As an example, the current collector 10 has two surfaces opposite to each other in its thickness direction, and the active material layer 20 is disposed on the two opposite surfaces of the current collector 10. Further, an adsorption layer 30 is formed on the surfaces of the active material layer 20 on both sides. It is understood that in other embodiments, the active material layer 20 may also be stacked on any one of the two surfaces of the current collector 10.
[0051] In this embodiment, the active material layer 20 has a first surface facing away from the current collector 10, and a side surface connected to the first surface is formed at the edge of the active material layer 20, that is, the active material layer 20 includes a first surface and a side surface, and an adsorption layer 30 is arranged on the first surface and / or the side surface of the active material layer 20. In the related art, some of them only arrange the adsorption layer 30 on the first surface of the active material layer 20, while in the embodiment of the present application, the adsorption layer 30 is arranged not only on the first surface of the active material layer 20, but also on the side surface of the active material layer 20, which can more effectively avoid gas leakage and improve adsorption efficiency.
[0052] The above-mentioned adsorption layer 30 covers at least a portion of the first surface and / or at least a portion of the side surface, which means that the adsorption layer 30 can be arranged on the first surface, or can also be arranged on the side surface, or can also be arranged on the first surface and the side surface; and, when the adsorption layer 30 is arranged on the first surface, it can cover the first surface in its entirety, or can also partially cover the first surface; when the adsorption layer 30 is arranged on the side surface, it can cover the side surface in its entirety, or can also partially cover the side surface. Preferably, in some preferred embodiments, the adsorption layer 30 covers the first surface and the side surface of the active material layer 20, that is, the adsorption layer 30 is provided on both the first surface and the side surface of the active material layer 20, and the adsorption layer 30 can cover most of the first surface and the side surface, or the adsorption layer 30 can cover the first surface and the side surface of the active material layer 20 in its entirety.
[0053] Therefore, based on the above configuration, by covering the side of the active material layer 20 with the adsorption layer 30, that is, the adsorption layer 30 covers the edge area of the active material layer 20, and the adsorption layer can cover the edge of the positive active material area of the positive electrode plate, so that the edge area of the active material area can be completely covered (wrapped) by the adsorption layer, so that by adopting a full-coverage method on the outside of the active material area, the leakage of gas (such as oxygen) can be avoided, and the phenomenon of gas generated inside the battery leaking from the edge of the electrode plate is reduced, and the adsorption efficiency is improved, which is beneficial to improve the electrochemical performance of the battery using the electrode plate. In addition, the adsorption layer 30 of the COF material layer can avoid the introduction of metal ions, which is beneficial to improve the conductivity of the plate, and the highly regular pore structure of the COF material, that is, the ordered pore size and pore structure can enhance the kinetic performance of the battery, which is beneficial to improve the electrochemical performance or overall performance of the electrode plate.
[0054] The above-mentioned COF materials themselves have a porous skeleton structure and basically do not affect the diffusion and transmission of lithium ions.
[0055] In addition, by setting the above-mentioned adsorption layer 30, it is possible to prevent the electrolyte from directly contacting the active material, thereby reducing interface side reactions; it is also possible to inhibit the gas production of electrode plates such as silicon negative electrodes, and effectively adsorb the hydrogen, carbon monoxide, low-carbon hydrocarbons and other gases produced by the negative electrode plates during the battery cycle, thereby improving the thermal stability and cycle life of the battery, and improving the electrochemical performance of the battery using the electrode plates.
[0056] In the embodiment of the present application, the electrode plate can be used in the battery cell structure. Specifically, the electrode plate can be a positive electrode plate or a negative electrode plate. That is, the polarity of the electrode plate can be positive or negative. In particular, based on the gas generation problem of the existing negative electrode plate, the electrode plate is more preferably used as the negative electrode plate.
[0057] In some embodiments, the electrode plate is a negative electrode plate.
[0058] It should be noted that the above COF materials are materials known in the prior art, which may be COF materials well known in the prior art, or COF materials related to COF materials, such as COF materials modified in various ways, etc. This application does not involve new materials, but only applies COF materials known in the prior art to the electrode plates of this application.
[0059] In some embodiments, the COF-based material layer includes a COF material layer or a modified COF material layer. The modified COF material layer may be a modified COF material obtained by modifying a CPF material by any known modification method in the related art, and this embodiment is not limited thereto. As an example, the modified COF material layer may be a carbonized COF material layer, and its specific carbonization method is well known to those skilled in the art.
[0060] Optionally, in the carbonized COF material, that is, the porous organic framework material COF carbonized by annealing, the organic solvent used in the carbonization process may be one or more mixed solvents of SMSO, DMF, and DMAC, and under acid catalysis, hexa(4-aminophenoloxy)cyclotriphosphazene, 2,3,5,6-tetrafluoroterephthalaldehyde and terephthalaldehyde react at 60°C for 1-4h, and then wash and dry to prepare a fluorine-containing multi-structural unit covalent organic framework material; after grinding the precursor, it is pyrolyzed in three stages under the protection of a protective atmosphere such as N2 or Ar, and cooled to obtain a carbonized COF material, that is, a modified COF material. This embodiment is not limited to this. Of course, other modification methods can also be used.
[0061] It should be understood that since the commonly used lithium-ion electrolyte components are easily reduced at the negative electrode to produce carbon monoxide and low-carbon hydrocarbon gases, in actual use, the cycle life of the finished battery cell will be reduced. At present, many research directions are to add porous materials to the battery to adsorb the negative electrode gas of the battery to reduce the impact on the battery cycle performance, but the introduction of foreign objects will more or less bring other disadvantages to the battery. Some studies have introduced ZIF materials, which have a three-dimensional pore structure, a high specific surface area and a pore structure. However, conventional ZIF materials have poor electrical conductivity, so high-temperature carbonization is required to enhance the electrical conductivity. However, ZIF materials have a metal coordination structure, which will cause the metal ions in the battery to escape, which will not only reduce the stability of the three-dimensional structure, but also cause the damage of the SEI film at the negative end if the metal is reduced at the negative electrode, resulting in additional consumption of the electrolyte, and ultimately causing a decrease in battery performance; in addition, when ZIF materials are carbonized at high temperatures, some metal oxide components will be generated, blocking the three-dimensional pore structure, requiring the use of an acid solution for treatment, increasing the difficulty of treatment, and also affecting the gas adsorption performance and kinetic performance; in addition, ZIF materials have a large density, a large mass, and do not have capacity characteristics, so they will reduce the energy density of the battery cell. Therefore, the application of ZIF materials in batteries still has the above-mentioned shortcomings.
[0062] COF is a covalent organic porous skeleton material that does not contain metal ions in its structure. There is no need to consider the effect of metal ion release on the adsorption of gas at the negative end of the battery. In addition, COF materials have highly regular nano- or micro-scale pores, large surface area and high chemical stability, and are widely used in various fields. In addition, compared with ZIF materials, COF has the advantage of light density, low impact on energy density, and carbonized COF has better conductivity and abundant pores, which has broad development prospects in the field of lithium-ion batteries.
[0063] Therefore, the adsorption layer 30 of the embodiment of the present application adopts a COF-type material layer and uses a porous organic covalent skeleton material COF or a carbonized COF as an adsorbent, which can not only avoid the introduction of metal ions and improve the electrochemical performance of the battery; but also COF is an organic matter, and after carbonization, the entire structure is transformed into carbon, and the conductivity is greatly improved, which is beneficial to improve the overall power performance of the battery. In addition, COF has a lighter density, so it can slow down the loss of energy density; and COF has a highly regular pore structure, and the ordered pore size and pore structure can enhance the kinetic performance of the battery. At the same time, in terms of the electrode plate structure of this embodiment, by adopting a full coating method on the outside of the active material layer 20, that is, the outside of the active area, the leakage of oxygen can be avoided and the adsorption efficiency can be improved. In addition, in some preferred embodiments, by adopting a design with a gradient thickness reduction of the edge adsorption layer 30, the mass of the plate is reduced and the energy density of the battery is improved.
[0064] In some embodiments, the adsorption layer 30 includes a first adsorption layer 31 and a second adsorption layer 32, wherein the first adsorption layer 31 covers at least a portion of the first surface, and the second adsorption layer 32 covers at least a portion of the side surface; the thickness of the first adsorption layer 31 is different from the thickness of the second adsorption layer 32. For example, the thickness of the first adsorption layer 31 can be thinner, while the average thickness of the second adsorption layer 32 can be thicker. That is, the average thickness of the second adsorption layer 32 is greater than the thickness of the first adsorption layer 31.
[0065] The above-mentioned adsorption layer is mainly composed of a first partial adsorption layer 31 and a second partial adsorption layer 32, wherein the first partial adsorption layer 31 can cover part or all of the first surface of the active material layer 20, and the second partial adsorption layer 32 can cover part or all of the side of the active material layer 20; and the thickness of the first partial adsorption layer 31 and the second partial adsorption layer 32 are different, that is, the thickness of the partial adsorption layer covering the first surface and the partial adsorption layer covering the side are different.
[0066] By making the thickness of the first adsorption layer 31 and the thickness of the second adsorption layer 32 different, it is helpful to reduce the production cost while ensuring the basic performance of the electrode plate.
[0067] In some embodiments, the thickness of the first adsorption layer 31 is 1 μm to 5 μm. As an example, the thickness of the first adsorption layer 31 can be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, or a range consisting of any two of the above values.
[0068] By controlling the thickness of the first part of the adsorption layer 31 within the above range, it helps to block the direct contact between the electrolyte and the active material, reduce the interface side reactions, inhibit gas production or effectively adsorb the gas generated by the electrode, etc., and also helps to reduce costs and reduce the weight of the electrode, thereby helping to reduce the weight of the battery.
[0069] The active material layer 20 may be covered around by the second partial adsorption layer 32 . Preferably, the active material layer 20 may be covered around by the second partial adsorption layer 32 in a gradient manner.
[0070] Specifically, in some embodiments, the thickness of the second portion of the adsorption layer 32 gradually becomes thinner along a direction away from the active material layer 20 .
[0071] In some embodiments, the thickness of the second adsorption layer 32 gradually decreases linearly in a direction away from the active material layer 20. As an example, the cross-sectional shape of the second adsorption layer 32 can be a triangle or a trapezoid.
[0072] In this embodiment, considering that the gas generated inside the battery will leak from the edge of the electrode plate, an adsorption layer 30 is also provided on the side of the active material layer 20, that is, the adsorption layer 30 can cover the edge area of the active material layer 20, such as spraying, intermittent coating, etc. to prepare a completely covered electrode plate. That is, the gas generation of the battery is uniform, but leakage from the edge of the plate should be considered, so the adsorption layer 30 is provided at the edge of the active material layer 20.
[0073] In particular, the thickness of the second adsorption layer 32 can be designed to be in a gradual form, for example, from the side close to the active material layer 20 to the side away from the active material layer 20, the thickness of the second adsorption layer 32 can be gradually thinned, such as in a linear and gradual thinning manner. The main function of the second adsorption layer 32 is sealing to reduce the phenomenon of gas leakage from the edge, and the second adsorption layer 32 is designed to be gradually thinned, that is, the second adsorption layer 32 is gradiently coated around the active material layer 20, mainly based on the consideration of weight reduction, which can not only reduce the weight of the pole piece, but also reduce the cost.
[0074] Therefore, by setting the second adsorption layer 32 to have a gradient thickness, the weight of the pole piece can be reduced, thereby facilitating the improvement of the energy density of the battery.
[0075] In addition, in other embodiments, the thickness of the second adsorption layer 32 may be varied in other ways. For example, the thickness of the second adsorption layer 32 decreases gradually in a gradient manner along the direction away from the active material layer 20. That is, the thickness of the second adsorption layer 32 may decrease gradually in a step-like manner. Alternatively, the thickness of the second adsorption layer 32 may become thinner in a curve along the direction away from the active material layer 20. This embodiment is not limited to this.
[0076] In some embodiments, the minimum thickness of the second adsorption layer 32 is a, the maximum thickness of the second adsorption layer 32 is b, a ranges from 0 to 10 μm, excluding 0, and b ranges from 71 μm to 165 μm.
[0077] In this embodiment, the thickness of the second adsorption layer 32 is gradual, and the thickness of the second adsorption layer 32 can decrease gradually from the side close to the active material layer 20 to the side away from the active material layer 20, and its thickness range can be 10 μm to the sum of the thickness of the active material layer 20 and the thickness of the first adsorption layer 31. That is, the second part of the adsorption layer 32 has a minimum thickness range, and the minimum thickness range a can be 0 to 10 μm, for example, it can be 0.5 μm, 1 μm, 2 μm, 3 μm, 5 μm, 6 μm, 8 μm, 10 μm, etc., and its maximum thickness range can be the sum of the thickness of the active material layer 20 and the thickness of the first part of the adsorption layer 31. For example, the maximum thickness range b can be 71 μm to 165 μm, for example, it can be 71 μm, 75 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 165 μm, etc.
[0078] In some embodiments, the average thickness of the second adsorption layer 32 is 50 μm to 150 μm. As an example, the average thickness of the second adsorption layer 32 can be 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 150 μm, or a range consisting of any two of the above values.
[0079] In some embodiments, the width of the second adsorption layer 32 is 3 mm to 8 mm. As an example, the width of the second adsorption layer 32 can be 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, or a range consisting of any two of the above values.
[0080] Therefore, by controlling the thickness and width of the second part of the adsorption layer 32 within the above range, it can not only play a role in weight reduction, which is beneficial to reducing the weight of the electrode, and then helping to reduce the weight of the battery and improve the energy density of the battery, but also effectively reduce the leakage of gas from the edge of the electrode.
[0081] In some embodiments, the current collector 10 includes a tab region and a coating region, the active material layer 20 covers the coating region, and the tab region is used to connect to the tab 40 ; one end of the tab 40 may be connected to the second partial adsorption layer 32 .
[0082] In some embodiments, the thickness of the active material layer 20 is 70 μm to 160 μm. As an example, the thickness of the active material layer 20 can be 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, or a range consisting of any two of the above values.
[0083] It is understandable that the coating thickness of the active material layer 20 is related to the battery capacity. The thicker the active material layer 20 is, the greater the battery capacity is. However, since the coating thickness is related to the charging rate, if the thickness is greater while ensuring the battery capacity, the lithium ion transmission rate will be reduced, and the charging rate will be correspondingly slowed down. Therefore, it is necessary to ensure the battery capacity and charging rate and control the thickness of the active material layer 20 within the above range.
[0084] In some embodiments, the thickness of the current collector 10 is 4 μm to 20 μm. For example, the thickness of the current collector 10 may be 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, or a range consisting of any two of the above values.
[0085] In some embodiments, the current collector 10 includes, but is not limited to, copper foil or carbon-coated copper foil.
[0086] In addition, the current collector 10 may also be made of metal materials such as aluminum, copper, nickel, stainless steel, nickel-plated steel, or a foil with a surface coating layer made of related foil materials, which has one or more functionalities such as improving conductivity, improving adhesion, improving safety, reducing DCR, and increasing lithium ion conduction capacity, for example, it may be a carbon coating layer, carbon coating + graphene / conductive carbon tube / boehmite or alumina and solid electrolyte coating, etc. Preferably, the current collector 10 of this embodiment may be made of one of copper foil and carbon-coated copper foil.
[0087] Optionally, the adsorption layer 30 may not contain a conductive agent, which is not limited in this embodiment.
[0088] Optionally, the adsorption layer 30 may contain a binder, which is not limited in this embodiment.
[0089] In this embodiment, the order of preparing the electrode plate may be: coating the active material layer 20, drying, coating the adsorption layer 30, drying, and rolling the plate to obtain the electrode plate.
[0090] Therefore, the electrode plate of this embodiment can make the adsorption layer 30 completely wrap the active material layer 20, so as to improve the adsorption efficiency; at the edge of the electrode plate, the adsorption layer 30 is set in a manner of decreasing thickness gradient, and the edge area is used as a coating area to avoid leakage of gas such as oxygen, so the design of decreasing gradient is set to reduce its mass and improve energy density;
[0091] In some embodiments, a battery is provided, which includes a positive electrode plate, a separator and a negative electrode plate, wherein the negative electrode plate adopts the aforementioned electrode plate; the positive electrode plate includes a positive electrode active material region, and the adsorption layer covers the edge of the positive electrode active material region.
[0092] In the battery of the present application, the negative electrode plate is provided with an adsorption layer, and the adsorption layer of the negative electrode plate can cover (coat) the edge of the positive electrode active material region of the positive electrode plate, thereby improving the adsorption efficiency.
[0093] The battery may be a secondary battery or a primary battery, preferably a secondary battery. For example, the battery may be a lithium-ion secondary battery, a lithium primary battery, a sodium-ion battery, a magnesium-ion battery, etc., but is not limited thereto. The battery structure of the present application includes but is not limited to a soft-pack lithium-ion battery, a square hard-shell battery, or a cylindrical hard-shell battery, etc.
[0094] It should be noted that, in the specific implementation manner, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the battery of the present application is not limited to a lithium-ion battery.
[0095] In this embodiment, the battery includes a positive electrode sheet and a negative electrode sheet, and the positive electrode sheet and / or the negative electrode sheet include an electrode sheet or an electrode sheet prepared according to the above method. Preferably, the electrode sheet is a negative electrode sheet.
[0096] In some embodiments, the battery further includes an electrolyte and a separator.
[0097] In the embodiments of the present application, there is no particular limitation on the electrolyte, isolation membrane, etc., as long as the purpose of the present application can be achieved.
[0098] The present invention is further described below in conjunction with specific embodiments. The implementation methods described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application.
[0099] Example 1
[0100] 1. Negative electrode
[0101] The negative electrode plate includes a current collector 10, an active material layer 20 arranged on the surface of the current collector 10, the active material layer 20 has a first surface facing away from the current collector 10, a side surface connected to the first surface is formed at the edge of the active material layer 20, and an adsorption layer 30 covering at least a portion of the first surface and the side surface of the active material layer 20, and the adsorption layer 30 is made of a COF material layer.
[0102] Among them, a 6 μm copper foil is used as the current collector 10; the negative electrode active material is graphite + silicon oxide material (8:2), the conductive agent is SP, and the adhesive is PAA and SBR.
[0103] The negative electrode active material, conductive agent, PAA, and SBR were mixed in a ratio of 95.5:1.5:2:1, and deionized water was added and stirred to form a uniform and stable negative electrode slurry. The negative electrode slurry was evenly coated on the negative electrode current collector with a coating surface density of 105 g / m 2After drying, an active material layer 20 is formed on the current collector, and a compaction density of 1.5 g / cm 3 ; The thickness of the active material layer 20 is 70 μm.
[0104] A slurry containing COF material or carbonized COF material is coated on the first surface of the active material layer 20 to form a first partial adsorption layer 31 on the first surface of the active material layer 20 with a coating thickness of 2 μm; and the slurry is coated on the side of the active material layer 20 to form a second partial adsorption layer 32 on the side of the active material layer 20; wherein according to the total thickness of the active material layer + the first partial adsorption layer, a second partial adsorption layer 32 with decreasing thickness is sequentially coated at the edge of the electrode (the thickness of the second partial adsorption layer gradually becomes thinner in the direction away from the active material layer) until it extends outward by 3-8 mm, and after drying and cold pressing, the preparation of the negative electrode is completed.
[0105] 2. Positive electrode
[0106] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the surface of the positive electrode current collector.
[0107] Among them, 13μm aluminum foil or composite aluminum foil is used as the positive electrode current collector; the positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder; the positive electrode active material is a ternary high-nickel material, the conductive agent is SP and CNTs, and the binder is PVDF.
[0108] In this embodiment, the positive electrode active material is NCM high nickel material, the chemical formula is LiNi 0.8 Co 0.1 Mn 0.1 O2, the conductive agent is conductive carbon black SP and carbon nanotubes, and the binder is PVDF5130; the mass ratio of the positive electrode active material, the conductive agent and the binder is 97:2:1.
[0109] The batching process uses existing technology to evenly mix the main positive electrode active material, conductive agent, adhesive and other materials and solvent NMP to form a uniform and stable positive electrode slurry, and evenly coat the positive electrode slurry on the positive electrode collector with a coating surface density of 195g / m 2 After drying and cold pressing, the positive electrode sheet is obtained, and the compaction density is 3.4g / cm 3 .
[0110] 3. The isolation membrane can be made of polyethylene film, polypropylene film, polyvinylidene fluoride film and non-woven fabric.
[0111] In this embodiment, a polypropylene film is selected as the isolation film base film, and a plurality of coating layers (such as a coating layer with a thickness of 3+3+3) may be provided on the polypropylene base film (with a thickness of 9 μm).
[0112] 4. The electrolyte includes a lithium salt and a solvent, wherein the types of the lithium salt and the solvent are not specifically limited and can be selected according to actual needs. For example, the lithium salt can be LiPF6, LiTFSI, LiBF4, etc.
[0113] In this embodiment, the electrolyte is LiPF6 dissolved in a solvent of ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate in a ratio of 1:1:1, with a concentration of 1.2 mol / L.
[0114] 5. Battery
[0115] During the cell assembly process, the positive electrode sheet, the separator, and the negative electrode sheet are arranged in sequence, and the assembly method is winding. The electrolyte is injected into the dry cell, and after immersion for 24 hours, the lithium battery is obtained after formation and aging.
[0116] Example 2
[0117] The main difference between Example 2 and Example 1 is:
[0118] In the negative electrode sheet, the second part of the adsorption layer is designed with uniform thickness.
[0119] The rest are the same as in Example 1.
[0120] Example 3
[0121] The main difference between Example 3 and Example 1 is:
[0122] In the negative electrode sheet, the thickness of the first part of the adsorption layer is 5 μm.
[0123] The rest are the same as in Example 1.
[0124] Example 4
[0125] The main difference between Example 4 and Example 1 is:
[0126] In the negative electrode sheet, the second partial adsorption layer is not provided, that is, the first partial adsorption layer is only formed on the first surface of the active material layer.
[0127] The rest are the same as in Example 1.
[0128] Comparative Example 1
[0129] The main difference between Comparative Example 1 and Example 1 is:
[0130] In the negative electrode sheet, the adsorption layer adopts a ZIF material layer.
[0131] The rest are the same as in Example 1.
[0132] Comparative Example 2
[0133] The main difference between Comparative Example 2 and Example 1 is:
[0134] In the negative electrode plate, no adsorption layer is provided, that is, the negative electrode plate only includes a current collector and an active material layer.
[0135] The rest are the same as in Example 1.
[0136] Performance Testing
[0137] 1. Physical and chemical tests on the COF material layer in Example 1 and the ZIF material layer in Comparative Example 1
[0138] (1) Specific surface area test: According to GB / T 19587-2004, the powder sample to be tested is placed in a U-shaped sample tube, and a mixed gas containing a certain proportion of adsorbate flows through the sample. The adsorption amount of the adsorbate molecule (N2) by the sample to be tested is determined based on the change in gas concentration before and after adsorption.
[0139] (2) Metal ion dissolution test: Weigh a certain mass of the material to be tested, such as 0.01-0.1g, and place it in a mixed solution of hydrochloric acid and nitric acid in a ratio of 3:1 (the formula ratio of aqua regia). After soaking for 30 minutes, take 0.5mL of the solution and perform ICP titration to test the corresponding metal ion concentration.
[0140] (3) Conductivity test: Take a certain mass of the material to be tested, such as 0.5-2g, and adjust the pressure to squeeze it into a cake-like object of the same thickness, which is generally between 2mm and 10mm. Then test its conductivity using a four-probe resistivity tester.
[0141] The test results are shown in Table 1 below.
[0142] Table 1
[0143]
[0144] From the data in Table 1, it can be seen that through the specific surface area test and conductivity display of the two materials, COF material and ZIF material have similar specific surface area, but the conductivity of COF material is greatly improved, which is due to the conversion of its organic monomer structure into carbon material after carbonization. Compared with the metal coordination structure, this structure has a faster electron transfer speed and thus better conductivity. And the ICP test of metal ion dissolution shows that the ZIF material is immersed in the electrolyte and the relevant metal ions are detected, indicating that the ZIF material will also have ion dissolution in the battery, which is easy to be reduced at the negative electrode, and ultimately causes the accelerated loss of the electrolyte, which will destroy the cycle stability of the battery.
[0145] II. Performance Test of Batteries of Examples 1-4 and Comparative Examples 1-2
[0146] (1) Internal resistance test: Use an internal resistance tester to test the DC internal resistance at 1000 Hz.
[0147] (2) 5C rate retention test: Tested in accordance with the requirements of GB31241-2014; rate retention = 5C discharge capacity / initial capacity.
[0148] (3) Capacity retention rate test: Tested in accordance with the requirements of GB31241-2014; capacity retention rate = capacity after 500 cycles / initial capacity.
[0149] (4) Energy density test: Tested in accordance with the requirements of GB31241-2014; Energy density = capacity * voltage / mass.
[0150] (5) Total volume test of gas components: Use the displacement method to test the volume. Based on the initial weight M1 and the weight in water M2, the volume V can be calculated as V = (M1-M2) / ρ*g, where ρ is the density of water and g is the acceleration due to gravity, which is equal to 10.
[0151] (6) Hot box test (failure temperature): According to GB / T 18287-2013 General Specification for Lithium-ion Batteries and Battery Packs for Mobile Phones, Section "5.3.5.3 Thermal Abuse", the battery is placed in a hot box and the temperature is raised to 130℃±2℃ at a rate of (5℃±2℃) / min and kept at this temperature for 30 minutes. After the test, the battery should meet the requirements of 4.5.2.
[0152] The test results are shown in Table 2 below.
[0153] Table 2
[0154]
[0155] The parts of the present invention that are not described in detail are well known to those skilled in the art.
[0156] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. are required by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and ease of understanding, not limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.
[0157] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the utility model, rather than to limit it. Although the utility model has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the utility model.
Claims
1. An electrode plate, characterized in that: The electrode plate comprises: current collector; an active material layer, disposed on at least one side surface of the current collector along the thickness direction, the active material layer having a first surface, the first surface facing away from the current collector, and a side surface connected to the first surface formed at an edge of the active material layer; An adsorption layer covers at least a portion of the first surface and / or at least a portion of the side surface, and the adsorption layer includes a COF material layer.
2. The electrode plate according to claim 1, characterized in that: The adsorption layer comprises a first adsorption layer and a second adsorption layer, wherein the first adsorption layer covers at least a portion of the first surface, and the second adsorption layer covers at least a portion of the side surface; The thickness of the first adsorption layer is different from the thickness of the second adsorption layer.
3. The electrode plate according to claim 2, characterized in that: The thickness of the first adsorption layer is 1 μm to 5 μm.
4. The electrode plate according to claim 2, characterized in that: The thickness of the second adsorption layer gradually decreases along a direction away from the active material layer.
5. The electrode plate according to claim 4, characterized in that: Along the direction away from the active material layer, the thickness of the second adsorption layer gradually becomes thinner in a linear manner.
6. The electrode plate according to any one of claims 2 to 5, characterized in that: The minimum thickness of the second adsorption layer is a, the maximum thickness of the second adsorption layer is b, the range of a is 0 to 10 μm, excluding 0, and the range of b is 71 μm to 165 μm; And / or, the average thickness of the second adsorption layer is 50 μm to 150 μm; And / or, the width of the second adsorption layer is 3 mm to 8 mm.
7. The electrode plate according to any one of claims 2 to 5, characterized in that: The current collector comprises a tab region and a coating region, the active material layer covers the coating region, and the tab region is connected to the tab; One end of the electrode tab is connected to the second portion of the adsorption layer.
8. The electrode plate according to claim 1, characterized in that: The thickness of the active material layer is 70 μm to 160 μm; And / or, the thickness of the current collector is 4 μm to 20 μm; And / or, the current collector comprises copper foil or carbon-coated copper foil.
9. The electrode plate according to claim 1, characterized in that: The COF-based material layer includes a COF material layer or a modified COF material layer.
10. A battery, characterized in that: The battery comprises a positive electrode sheet, a separator and a negative electrode sheet, wherein the negative electrode sheet adopts the electrode sheet as described in any one of claims 1 to 9; the positive electrode sheet comprises a positive active material region, and the adsorption layer covers the edge of the positive active material region.